Komunikasi Humor: Mengekspresikan Frustrasi tanpa Konfrontasi - Prasetya, Hendri (WACANA, Jurnal Ilmiah Ilmu Komunikasi, 2007)
Undoubtedly   humor    and   laughing    are   essential   parts   of  what  if  is  to  be human.   All humor  is fundamentally  human   activity.  Humor  is one  of the  most important form  of  creative  human   communication   and  expressive  culture/  yet the   formal   study   of   humor   and   ifs  social   consequences   has   not   enjoyed widespread   popularity.     Humor    literature    can    be    split   info    two    broad categories:    (a)  why   individuals    use   humor   (mofivafional!y/psychological/y)and  (b) the function  humor   within a social  setting  on society  (sociologically)